The L-Cell in Nutritional Sensing and the Regulation of Appetite - Spreckley, Eleanor; Murphy, Kevin Graeme (Frontiers in Nutrition, 2015)
The gastrointestinal tract senses the ingestion of food and responds by signalling to the brain to promote satiation and satiety. Representing an important part of the gut-brain axis, enteroendocrine Lcells secrete the anorectic peptide hormones glucagon-like peptide-1 (GLP-1) and peptide YY (PYY) in response to the ingestion of food. The release of GLP-1 has multiple effects, including the secretion of insulin from pancreatic β-cells, decreased gastric emptying and increased satiation. PYY also slows gastrointestinal motility and reduces food intake. At least part of the gut-brain response seems to be due to direct sensing of macronutrients by L-cells, by mechanisms including specific nutrient-sensing receptors. Such receptors may represent possible pathways to target to decrease appetite and increase energy expenditure. Designing drugs or functional foods to exploit the machinery of these nutrient-sensing mechanisms may offer a potential approach for agents to treat obesity and metabolic disease.